1992
DOI: 10.1090/s0002-9939-1992-1100653-4
|View full text |Cite
|
Sign up to set email alerts
|

Special 𝛼-limit points for maps of the interval

Abstract: Abstract.The notion of a special «-limit point is defined. For maps of the interval, it is shown that a point is a special a-limit point if and only if it is an element of the attracting center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Before turning our attention to Question 1.2, and in keeping with the precedent set in [23], we will briefly highlight a corollary concerning γ-limit sets. These were introduced by Hero [27] who studied them for interval maps, γ-limit sets have since been further examined by Sun et al in [46] and [45] for graph maps and dendrites respectively. The γ-limit set of a point x, denoted γ(x), is defined by saying that, for any y ∈ X, y ∈ γ(x) if and only if y ∈ ω(x) and there exists a sequence y i ∞ i=1 in X and a strictly increasing sequence n i ∞ i=1 in N such that f n i (y i ) = x for each i and lim i→∞ y i = y.…”
Section: γ-Limit Sets and Ict Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Before turning our attention to Question 1.2, and in keeping with the precedent set in [23], we will briefly highlight a corollary concerning γ-limit sets. These were introduced by Hero [27] who studied them for interval maps, γ-limit sets have since been further examined by Sun et al in [46] and [45] for graph maps and dendrites respectively. The γ-limit set of a point x, denoted γ(x), is defined by saying that, for any y ∈ X, y ∈ γ(x) if and only if y ∈ ω(x) and there exists a sequence y i ∞ i=1 in X and a strictly increasing sequence n i ∞ i=1 in N such that f n i (y i ) = x for each i and lim i→∞ y i = y.…”
Section: γ-Limit Sets and Ict Fmentioning
confidence: 99%
“…This presents a difficulty when attempting to give a suitable definition for α f (x). Various approaches to this have been taken [2,16,17,27,45,46]. For a discussion on this, we refer the reader to [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But when we study continuous mappings f : X → X (not necessarily invertible), a point x may have many preimages (or none at all), and we must clarify what kind of backward limit set we wish to speak of. Several definitions have been proposed including conical limit sets, α-limit sets, branch α-limit sets, special α-limit sets, and others [1,7,11,15,16,20].…”
Section: Introductionmentioning
confidence: 99%
“…The attracting center A°° is defined to be the intersection of the sets A" . In [7] it is shown that for self-maps / of the interval A°° = SA(f,I). Proposition 3.…”
Section: Introductionmentioning
confidence: 99%